RETRACTED: LncRNA TCF7 Promotes Epithelial Ovarian Cancer Viability, Mobility and Stemness via Regulating ITGB8 - Su, Changlei; Huang, Kejin (Frontiers in Oncology, 2021)
This study aimed to investigate the carcinogenic role of long non-coding RNA T-cell factor 7 (lnc-TCF7) in epithelial ovarian cancer (EOC). Lnc-TCF7 overexpression and shRNA plasmids were transfected into SKOV3 and OVCAR3 cells, followed by measurement of cell proliferation, migration, invasion, apoptosis, stemness, and mRNA profile (via microarray). Besides, lnc-TCF7 expression was measured in tumor and adjacent tissues from 76 EOC patients. Lnc-TCF7 was upregulated in EOC cell lines; its overexpression increased cell proliferation, migration, invasion, but decreased apoptosis and promoted CD44, CD133 expressions, CD44+CD133+ cell proportion, spheres formation efficiency and drug resistance to cisplatin in SKOV3 and OVCAR3 cells. Besides, lnc-TCF7 ShRNA exhibited opposite effects comparing with its overexpression. Microarray analysis revealed 267 mRNAs were modulated by lnc-TCF7 dysregulation, among which ITGB8 was the most dysregulated one, which was validated by subsequent western blot and RT-qPCR. Furthermore, ITGB8 overexpression not only induced proliferation, migration, invasion and stemness, but also attenuated the effect of lnc-TCF7 ShRNA on these functions in SKOV3 and OVCAR3 cells. In addition, lnc-TCF7 was upregulated in tumor tissues and correlated with higher pathological grade, tumor size, International Federation of Gynecology and Obstetrics (FIGO) stage and worse overall survival in EOC patients. Conclusively, lnc-TCF7 regulates multiple oncogenic pathways, promotes proliferation, migration, invasion, stemness via upregulating ITGB8. It also correlates with advanced tumor features and poor prognosis in EOC, implying its potential as a target for EOC treatment.